أحلام العصر - الجزار, آلاء; الجعبري, لارا; زغـيــــــر, دانيــــــة; ابو ريش, وفاء; سلطان, يسري (جامعة بوليتكنك فلسطين - جرافيكس, 2022)
فيلم يعرض تخصصات كلية العلوم الإدارية (جرافيكس وسائط متعددة " محاسبة تسويق نظم المعلومات) بطريقة كوميدية وبطابع فكاهي يعرض الصورة الخاطئة المألوفة عن التخصصات ومدة الفيلم 5دقائق ,وتم الترويج للفيلم من خلال مواقع التواصل الاجتماعي وايضا اسم المشروع الذي له دور كبير في تحقيق صدى واسع له وخصوصا بفئة الشباب وهي من اهداف المشروع , تم عرضه في يوم مناقشة المشروع في جامعة بوليتكنك فلسطين في كلية العلوم الادارية مبنى ابو رمان في قاعة المؤتمرات و سوف يتم عرضه على مواقع التواصل الاجتماعي الخاصة بجامعة بوليتكنك فلسطين . A film presenting the majors of the Faculty of Administrative Sciences (multimedia graphics, “accounting for marketing information systems) in a comical manner and with a humorous nature that presents the familiar wrong image of the disciplines. The duration of the film is 5 minutes. The film was promoted through social networking sites, as well as the name of the project, which has a major role in achieving a wide resonance for it. Especially in the youth category, which is one of the goals of the project. It was presented on the project discussion day at Palestine Polytechnic University in the College of Administrative Sciences, Abu Rumman Building in the conference hall, and it will be shown on the social networking sites of Palestine Polytechnic University
no of pages 73, جرافيكس 2023
Keywords: الرسوم المتحركة - افلام